Evaluasi Penerapan Konsep "Green City" di Kecamatan Moncongloe Kabupaten Maros - Panjhi Arieq Naufal Mugni; Muhammad Fuad Aziz; Ilham Yahya (Journal of Urban Planning Studies, 2021)
Abstract. The development of urban areas in Indonesia is developing very fast, and is dynamic, so that its activities and development will cause various kinds of problems and impacts of environmental problems, such as imbalances between the growth of urban areas and the improvement of environmental quality. This condition makes the city uncomfortable to live in. Maros Regency has also become a district that is developing very rapidly following the development of the Metropolitan city of Makassar as the main city, forcing Maros Regency which is part of the Mamminasta urban area (Makassar, Maros, Sungguminasa, and Takalar) to develop rapidly. Especially in the new urban area in Moncongloe District which is a satellite city area. However, there are also threats that occur in Moncongloe District, namely frequent flooding, burning of garbage by the community and poor drainage management, so a concept of prevention and handling is needed to overcome these problems, namely the concept of a green city or commonly called "Green city". The concept of this approach is still not maximally applied in Moncongloe District, so the output of this study is to evaluate how much implementation has been done in the research location and formulate strategies to improve the performance of each indicator of a green city.